A reversible state of hypometabolism in a human cellular model of sporadic Parkinson’s disease - Schmidt, Sebastian; Stautner, Constantin; Vu, Duc Tung; Heinz, Alexander; Regensburger, Martin; Karayel, Ozge; Trümbach, Dietrich; Artati, Anna; Kaltenhäuser, Sabine; Nassef, Mohamed Zakaria; Hembach, Sina; Steinert, Letyfee; et al. (Nature Communications, 2023)
Sporadic Parkinson’s Disease (sPD) is a progressive neurodegenerative disorder caused by multiple genetic and environmental factors. Mitochondrial dysfunction is one contributing factor, but its role at different stages of disease progression is not fully understood. Here, we showed that neural precursor cells and dopaminergic neurons derived from induced pluripotent stem cells (hiPSCs) from sPD patients exhibited a hypometabolism. Further analysis based on transcriptomics, proteomics, and metabolomics identified the citric acid cycle, specifically the α-ketoglutarate dehydrogenase complex (OGDHC), as bottleneck in sPD metabolism. A follow-up study of the patients approximately 10 years after initial biopsy demonstrated a correlation between OGDHC activity in our cellular model and the disease progression. In addition, the alterations in cellular metabolism observed in our cellular model were restored by interfering with the enhanced SHH signal transduction in sPD. Thus, inhibiting overactive SHH signaling may have potential as neuroprotective therapy during early stages of sPD.
CRIS-Team Scopus Importer:2023-12-08